Validasi Oleh Notaris Terhadap Kebenaran Keterangan Dan Dokumen Para Penghadap - Suandika, Ida Bagus Dobi; Yasa, Putu Gede Arya Sumerta (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022)DO - 10.24843/AC.2022.v07.i02.p1, 2022)
The purpose of this paper is to find out the responsibility of the Notary to the deed he made using a false identity and to know the legal consequences of the Notary deed made with a false identity. The research that uses normative law is related to the problem of norms that occur, namely the absence of norms that do not regulate identity falsification in a notary deed. The research is sourced from primary, secondary and tertiary legal materials and the writing approach is carried out through a conceptual approach that analyzes the concept of violations by the appearers in the statement of false identities in the making of authentic deeds. The results of the study can be concluded that the Notary's responsibility for the deed made using a false identity is that the notary is responsible for the rest of his life for the deed he has made so that the notary in making an authentic deed, although not responsible for the material truth of the deed made, but the notary also needs to Knowing the material truth, the Notary can be held accountable both under civil law and criminal law. and the legal consequences of a Notary deed made with a false identity is that it will get sanctions according to the Civil Code and sanctions according to the Criminal Code.